Visible spectrophotometric Determination of Rexithromycin in Pharmaceutical Solid Dosage From - Rajasekaran, A.; Gopinath, M. (Asian Journal of Chemistry, 2010)
A new visible spectrophotometric method is developed for the estimation of roxithromycin (RXM) in pharmaceutical solid dosage form. The method is based on the reaction of RXM with marquis reagent which forms a brown coloured chromogen with absorption maximum at 495 nm. The chromogen formed is stable and beer's law is obeyed in the concentration range of 15-25 μg/mL .